A secure online examination system - Liu, Xiao (Nanyang Technological University, 2023)
This report discusses the development of a web-based Online Examination System (OES) for higher education institutions to address the limitations of traditional examination methods. These limitations include question leakages, cheating, biases, and human errors. To overcome these challenges, the project aims to develop a robust and secure OES that incorporates smart motion detection and facial validation functions. The OES will also incorporate a video conferencing feature for live proctoring to ensure the integrity of the examination process.